Premature ejaculation among post-coronary artery stenting patients attending cardiology out patient department of tertiary care hospitals (Bangladesh Journal of Psychiatry, 2020)
Premature ejaculation (PE) is the most frequent sexual complaint of men. It may develop not only due to psychiatric disorders but also due to many chronic organic illnesses. Coronary artery stenting is an invasive procedure to manage coronary artery disease which is one of the leading chronic illnesses all over the world. Patients who survive from coronary artery diseases by getting invasive cardiac procedures, often develop reduced sexual function. The aim of the study was to identify the frequency of premature ejaculation among post coronary artery stenting patients. This was a descriptive, cross sectional study conducted in cardiology outpatient department (OPD) of Bangabandhu Sheikh Mujib Medical University (BSMMU) and cardiology OPD of National Institute of Cardiovascular Diseases (NICVD) from October 2017 to September 2018. 153 patients were selected purposively. After taking written consent a predetermined questionnaire containing 11 socio-demographic variables was filled for each patient through face to face interview. After that PEDT bangle version was applied.37.25% post coronary artery stenting male scored 11 or more and were identified as highly suggestive to have PE. Among the socio-demographic variables, Regular exercise, amount of sleep per day, smoking and history of chronic physical illness were found to be significantly associated with PE among post coronary artery stenting patients. The study showed that the patients who practiced a disciplined and healthy lifestyle were not in risk. The research findings may help us for the early diagnosis and better treatment plan to reduce patient sufferings.Bang J Psychiatry June 2018; 32(1): 9-13